PENGARUH KOMPRES AIR HANGAT TERHADAP PENURUNAN NYERI HAID (DISMINOREA) PADA SISWI SMK NEGERI 1 RAMBAH SAMO KABUPATEN ROKAN HULU TAHUN 2020: THE INFLUENCE OF COMPRESS WARM WATER TO A DECREASE IN PAINFUL MENSTRUATION ( DISMINOREA) IN FROM SMK N 1 RAMBAH SAMO KABUPATEN ROKAN HULU THE YEAR 2020 - Winda Ayu Lestari; Yuyun Priwahyuni; Christine Vita Gloria Purba (Media Kesmas (Public Health Media), 2021)
ABSTRACT Painful menstruation (disminorea) is a medical condition that occurs when menstrual characterized by pain or pain in the region of the abdomen and pelvis. Painful menstruation had an impact that bad , which is causing a disturbance in teaching and learning activities , and did not go to school. According to World Health Organization (who) years 2016 the world disminorea rata-rata more than 50% women have it. SMK N 1 Rambah Samo Is one of vocational high schools are a lot of the number of teenagers his daughter who suffered painful menstruation, but the school has not yet there were scouts health especially about how to overcome painful menstruation ( disminorea ) and have not yet pik formation of a teenager ( information center and a teenager ) counseling in order to to give information and counseling services to students. Painful menstruation (disminorea) could be non therapy farmokologi, one compress warm water. Compress warm water is a method to give the heat and causes dilation of the blood vessels so that painful menstruation that was felt to be reduced. Research objectives was to find the influence of compress warm water to a decrease in painful menstruation (disminorea) in female students of SMK N 1 Rambah Samo in 2020. This study used Quasi Ekspeimen design Nonequivalent Control Group. With population as 60 sample of 34 , consisting of 17 the control group and 17 the experiment. Sampel taken by purposive sampling technique. The Analysis used Wilcoxon test. The result showed that any impact to compress warm water a decline in painful menstruation in the experiment with the ? value (0,0001) <0,05 while in the control group did not show a decline in the painful menstruation ? value (1,000) >0,05. It is expected that compress warm water used for an alternative to reduce the feeling of hurt when mestruasi. Keywords : Painful menstruation, compress warm water, Students